Neurogranin in Alzheimer's Disease: Roles in synaptic function, pathology, and potential as a diagnostic biomarker - Rajkumar Bavaharini; Chaitanya Sree Somala; Konda Mani Saravanan; Thirunavukarasou Anand (AIMS Molecular Science)
Postsynaptic protein neurogranin (Ng), which plays a role in synaptic plasticity, learning, and memory, has been identified as the candidate biomarker of Alzheimer's disease (AD). Cortical Amyloid β pathology seems to accelerate the onset of clinical symptoms; therefore, it is potentially valuable for early diagnosis of AD and therapeutic intervention. Synaptic pathology was shown to be an early feature of AD. Thus, proteins involved in synaptic function, such as Ng, are of great interest in studying the disease. Some prior human studies have found that Ng, a protein involved in the regulation of synaptic function, is present at greater levels in the cerebrospinal fluid of people with AD compared with those without the disease. High levels of neurogranin are associated with increased levels of synaptic vulnerability and decreased cognitive function in AD patients. This review, therefore, looked at the functionality of Ng in the brain, its association with other synaptic proteins, and its applicability as a diagnostic marker in AD. This study, therefore, sought to expand the knowledge on Ng changes in AD as it relates to synaptic dysfunction and enhanced the search for a better diagnostic and therapeutic approach.